Creating Full English Atmosphere in Teaching English to Young Learners: Teachers’ Perspectives - Annisa Astrid; Amalia Hasanah; Syafryadin Syafryadin (Register Journal, 2020)
The research had two objectives; 1) to explore teachers’ belief about the use of full English during learning activities, and 2) to determine the factors that affected the use of full English in teaching English to teach English to young learners. Embedded mixed method was used in this study. The quantitative data were gained by distributing 1 set of closed-response questionnaire item to 38 teachers of English who teach English at elementary schools in Palembang, a capital city of South Sumatera Province, Indonesia. Meanwhile, the qualitative data were gained from one-to-one in depth interview to 15 teachers of English who were willing to be interviewed. Students’ responses to each questionnaire item were analyzed by using descriptive statistics analysis by Employing SPSS program. Meanwhile, the qualitative data gained from the interview were analyzed by using thematic analysis. It was revealed from the study that first, teachers shared positive belief about the use of full English while teaching English in the class. Secondly, there are five factors that affected the use of full English during learning activities; 1) The English Proficiency of the teachers; 2) School Policy; 3) The homogeneous level of students’ language performance 4) Teacher’s classroom management skills and 5) Students’ attitude toward English.